Adapting the Get Yourself Tested Campaign to Reach Black and Latino Sexual-Minority Youth. Issue 5 (September 2016) - Garbers, Samantha; Friedman, Allison; Martinez, Omar; Scheinmann, Roberta; Bermudez, Dayana; Silva, Manel; Silverman, Jen; Chiasson, Mary Ann
Background. Culturally appropriate efforts are needed to increase sexually transmitted disease (STD) testing and care among Black and Latino sexual-minority youth, who are at high risk for STDs. Get Yourself Tested, a national testing campaign, has demonstrated success among youth, but it has yet to be assessed for relevance or impact among this population. Method. This effort included (1) formative and materials-testing research through focus groups; (2) adaptation of existing Get Yourself Tested campaign materials to be more inclusive of Black and Latino sexual-minority youth; (3) a 3-month campaign in four venues of New York City, promoting STD testing at events and through mobile testing and online and social media platforms; (4) process evaluation of outreach activities; and (5) an outcome evaluation of testing at select campaign venues, using a preexperimental design. Results. During the 3-month campaign period, the number of STD tests conducted at select campaign venues increased from a comparable 3-month baseline period. Although testing uptake through mobile vans remained low in absolute numbers, the van drew a high-prevalence sample, with positivity rates of 26.9% for chlamydia and 11.5% for gonorrhea. This article documents the process and lessons learned from adapting and implementing a local campaign for Black and Latino sexual-minority youth.